THE IMPACT OF DIGITALIZATION ON INTEREST IN SHARIA INVESTMENT AMONG THE YOUNGER GENERATION - Marlina Susana, Lina; Mulyana, Dadang; Pinayani, Ahmad Fadhila (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT This study aims to analyze the impact of digitalization on the interest in sharia investment among the younger generation and to gain an in-depth understanding of the experiences, views, and motivations of the younger generation regarding sharia investment in the digital era. This study uses a qualitative approach. Data collection techniques were carried out through in-depth interviews with a number of informants selected using purposive sampling, namely young people who are or have been interested in Islamic investment through digital platforms. In addition to interviews, data was also collected through observation of the use of Islamic investment applications and analysis of documentation from social media and related digital platforms. Data analysis was conducted using a descriptive qualitative approach with a thematic approach. The results obtained show that the digitization of the Islamic economy in Indonesia has had a major impact on how the younger generation interacts with the financial system. The ease of access, transparency, and security offered by digital platforms make Islamic investment and financing more attractive and accessible to young people. However, more in-depth education about Islamic principles in the digital economy is essential to avoid misuse or mistakes in choosing products. In practical terms, the findings of this study provide insights to Islamic finance industry players, regulators, and financial technology (fintech) developers to pay more attention to the needs and characteristics of the younger generation as a potential target market. ABSTRAK Penelitian ini bertujuan untuk menganaisis dampak digitalisasi terhadap minat investasi syariah di kalangan generasi muda dan untuk memperoleh pemahaman yang mendalam terkait pengalaman, pandangan, dan motivasi generasi muda terhadap investasi syariah di era digital. Penelitian ini menggunakan pendekatan kualitatif. Teknik pengumpulan data dilakukan melalui wawancara mendalam (in depth interview) dengan sejumlah informan yang dipilih secara purposive sampling, yaitu generasi muda yang telah atau sedang tertarik dengan investasi syariah melalui platform digital. Selain wawancara, data juga dikumpulkan melalui observasi terhadap penggunaan aplikasi investasi syariah serta analisis dokumentasi dari media sosial dan platform digital yang berkaitan. Analisis data dilakukan secara deskriptif kualitatif dengan pendekatan tematik. Hasil yang diperoleh yaitu, Digitalisasi ekonomi syariah di Indonesia telah membawa dampak besar terhadap caragenerasi muda berinteraksi dengan sistem keuangan. Kemudahan akses, transparansi, serta keamanan yang ditawarkan oleh platform-platform digital membuat investasi dan pembiayaan syariah lebih menarik dan mudah diakses oleh kalangan muda. Meskipun demikian, edukasi yang lebih mendalam tentang prinsip-prinsip syariah dalam ekonomi digital sangat penting untuk menghindari penyalahgunaan atau kesalahan dalam memilih produk. Secara praktis, temuan penelitian ini memberikan wawasan kepada pelaku industri keuangan syariah, regulator, dan pengembang teknologi finansial (fintech) untuk lebih memperhatikan kebutuhan serta karakteristik generasi muda sebagai target pasar potensial.